(untitled) (Medical Forum Monthly, 2022)
Objective: To determine the association of life events with patients of conversion disorder Study Design: Descriptive cross sectional study Place and Duration of Study: This study was conducted at the Psychiatry department, Chandka Medical College, SMBB Medical University Larkana from October to December, 2021. Materials and Methods: Diagnosed cases of conversion disorder were enrolled either in-patients or out-patients. For life events in the last 01 months Holmes and Rahe scale was applied on all cases of conversion disorder. Data analyses was done by using SPSS version 22 statistical software package. Results: A total of 96 female participants, majority 74 (77.1%) were married, and Sindhi by ethnicity 94 (97.9%). Among all participants 57 (59.4%) were not formally educated and were brought in hospital by family. Among all 88 (91.7%) were house-hold by occupation. Among all conversion disorders patients majority were presenting to hospital for first time 64 (66.7%). Among all conversion disorders patients, majority 46 (47.9%) were having less than 150 total life events score on Holmes and Rahe score. The number of presentation or admissions in psychiatric unit were stratified with score of Holmes and Rahe life events scale and were found statistically significant having P values of 0.000. Conclusion: Life events stresses are found in all conversion disorder patients. They are also significantly associated with hospital presentation or admission.